Factors Influencing the Intention to Continue using B2B e-Commerce in Manufacturing SMEs - Hussein, L. A.; Baharudin, A. S.; Kiumarsi, S.; Hilmi, M. F. (Engineering, Technology & Applied Science Research, 2020)
Business-to-Business (B2B) electronic commerce plays a tremendous role in nurturing the growth of Small and Medium Enterprises (SMEs) in developed and developing countries. However, the growth of B2B e-commerce in developing nations remains at the early adoption stage. The purpose of this paper is to examine the factors that influence B2B e-commerce adoption in SMEs in a developing country. The current study employs the questionnaire survey technique to gather information from 245 manufacturing SMEs in Jordan. It uses Structural Equation Modeling (SEM) to investigate the different factors that affect the intention to adopt or continue using B2B e-commerce. The study reveals that compatibility and outsourcing IT support have significant effects on the intention to continue using B2B e-commerce in Jordanian manufacturing SMEs. The implications of the findings are discussed.